A Qualitative Study on Home Modification of Rural Caregivers for People with Dementia. Issue 1 (2nd January 2016) - Damme, Mary Jane; Ray-Degges, Susan
ABSTRACT: This study asserts that in order to enhance functionality of home modification, caregivers need specific training by professionals before environmental changes create confusion. The purpose of this study was to investigate the beliefs and attitudes of caregivers regarding the effects of environments on the independence of a family member with dementia living in the home. Using a phenomenological approach to gather narrative information about caregiving and the home environment, semi-structured interview questions were conducted with six caregivers in a rural Midwestern county. Two main themes emerged from the caregiver perceptions regarding attitudes about the physical environment: (a) change within the home creates confusion in the care recipient; and (b) there are few changes in the home that will increase the independence of a person with dementia. The findings of the study resulted in a deeper understanding of caregivers' attitudes about the physical environment and their resistance to environmental changes.